(3GdCUds - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdhVhA s
(3BNQgG (B:s
(3hbY eY NQhLgG ef edc GdChd hcd eedhc s
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B107s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs